Metrological Evaluation of a Novel Medical Robot and Its Kinematic Calibration. (16th September 2015) - Zhao, Longfei; Joubair, Ahmed; Bigras, Pascal; Bonev, Ilian A.
The vessels are twisted in a longitudinal 3D space in the lower limbs of humans. Thus, it is difficult to perform an ultrasound scanning examination in this area. In this paper, a new medical parallel robot is introduced to effectively diagnose vessel disease in the lower limbs. The robot's position repeatability and accuracy are evaluated. Furthermore, the robot's accuracy is improved through a calibration process in which the kinematic parameters are identified through a simple identification approach.